What may cause fetus loss from acute pancreatitis in pregnancy: Analysis of 54 cases. Issue 7 (February 2018) - Tang, Min; Xu, Jian-Ming; Song, Sha-Sha; Mei, Qiao; Zhang, Li-Jiu
Abstract : Abstract: Acute pancreatitis in pregnancy (APIP) poses a serious threat to the mother and her fetus, and might lead to fetal loss including miscarriage and stillbirth in certain patients. We sought to identify possible factors that affect fetal distress and evaluated outcomes of patients with APIP. We retrospectively reviewed clinical records of 54 pregnant women with APIP, who were treated at 2 tertiary clinical centers over a 6-year period. Clinical characteristics including etiology and severity of APIP, fetal monitoring data, and maternofetal outcomes were analyzed. Etiology of APIP included acute biliary pancreatitis (ABP, n = 14), hyperlipidemic pancreatitis (HLP, n = 22), and other etiologies (n = 18). Severity was classified as mild acute pancreatitis (MAP, n = 23), moderately severe acute pancreatitis (MSAP, n = 24), and severe acute pancreatitis (SAP, n = 7). The incidence of preterm delivery, fetal distress, and fetal loss increased with the progression of severity of APIP ( P  < .05). The severity of HLP was significantly higher than that of ABP and APIP of other etiology ( P  < .01). HLP was more likely to lead to fetal distress than other APs ( P  < .01). Only 12 (22.2%) patients had fetal monitoring including non-stress test (NST); 1 case of SAP (14.3%) and 15 cases of MSAP (62.5%) were not transferred to intensive care unit for intensive monitoring. The incidence of fetal distress and fetal loss increased with worsening of APIP severity. HLP tends to result in worse fetal outcomes. The deficiencies of fetal state monitoring, lack of assessment, and management of pregnant women might increase the fetal loss in APIP. Abstract : Supplemental Digital Content is available in the text